Sistem Informasi Pemesanan Menu Pada The Gade Coffe Imam Bonjol - Frilia Tappi; Y yusup; Ana Wahyuni (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2026)
Various aspects of daily life have Modern society has experienced profound changes due to the fast-paced development of information technology, affecting how people live, communicate, and work digital era influenced various business sectors, including the culinary industry, particularly in café and coffee shop services. The Gade Coffee Imam Bonjol, as one of the growing coffee shops, still experiences limitations in the menu ordering process, which is generally conducted manually and can lead to inefficiency in service, order recording errors, and longer waiting times for customers. This study emphasizes the development and deployment of a web-based platform for The Gade Coffee Imam Bonjol, designed to facilitate menu ordering and improve the speed and accuracy of both ordering and transaction activities. The implemented system provides assistance to customers in viewing menus, placing orders, and monitoring order status digitally, as well as assisting staff in managing orders and menu data efficiently. The system provides features such as digital menu display, online ordering, order management, and transaction data recording. This study utilizes a structured Waterfall model for system development, involving several sequential stages: analyzing the system requirements, designing the system architecture, implementing the solution, carrying out testing procedures, and maintaining the system after deployment. This study applies Black Box Testing to examine the system, revealing that all features work correctly and consistently with the pre-determined specifications, ensuring the system meets its intended requirements. The use of the proposed system is anticipated to support more efficient service operations, reduce inaccuracies in the ordering process, and positively impact customer satisfaction at The Gade Coffee Imam Bonjol.